Evaluation of Connexin 43 Redistribution and Endocytosis in Astrocytes Subjected to Ischemia/Reperfusion or Oxygen-Glucose Deprivation and Reoxygenation. (23rd March 2017) - Xie, Hongyan; Cui, Yu; Hou, Shuai; Wang, Juan; Miao, Jing; Deng, Fang; Feng, Jiachun
Abstract : Connexin 43 (Cx43) is the major component protein in astrocytic gap junction communication. Recent studies have shown the cellular processes of gap junction internalization and degradation, but many details remain unknown. This study investigated the distribution of Cx43 and its mechanism after ischemic insult. Astrocyte culture system and a model of ischemia/reperfusion (IR) or oxygen-glucose deprivation and reoxygenation (OGDR) were established. Cx43 distribution was observed by laser scanning confocal microscopy under different cultivation conditions. Western blot and RT-PCR assays were applied to quantify Cx43 and MAPRE1 (microtubule-associated protein RP/EB family member 1) expression at different time points. The total number of Cx43 was unchanged in the normal and IR/OGDR groups, but Cx43 particles in the cytoplasm of the IR/OGDR group were significantly greater than that of the normal group. Particles in the cytoplasm were significantly fewer after endocytosis was blocked by dynasore. There was no difference among the groups at each time point regarding protein or gene expression of MAPRE1. We concluded that internalization of Cx43 into the cytoplasm occurred during ischemia, which was partially mediated through endocytosis, not by the change of Cx43 quantity. Moreover, internalization was not related to microtubule transport.